2012
DOI: 10.1016/j.clinph.2012.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Lateralisation of sound in temporal-lobe epilepsy: Comparison between pre- and postoperative performances and ERPs

Abstract: This study suggests that a test for assessing the ability of sound lateralisation based on each of the IID and ITD cues should be included in the evaluation of TLE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Still, we cannot completely exclude an influence of epilepsy pathophysiology on our findings. It has, for instance, been reported that the performance of patients with temporal-lobe epilepsy in a sound-lateralization task is impaired when compared to healthy controls (Tezer et al, 2012). This finding implies that we cannot be absolutely sure that binaural beats are processed identically in patients with temporal lobe epilepsy as in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Still, we cannot completely exclude an influence of epilepsy pathophysiology on our findings. It has, for instance, been reported that the performance of patients with temporal-lobe epilepsy in a sound-lateralization task is impaired when compared to healthy controls (Tezer et al, 2012). This finding implies that we cannot be absolutely sure that binaural beats are processed identically in patients with temporal lobe epilepsy as in healthy controls.…”
Section: Discussionmentioning
confidence: 99%